2022
DOI: 10.1155/2022/5547406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil Streptomyces Isolates from North-Western Ethiopia as Potential Inhibitors against Spoilage and Foodborne Bacterial Pathogens

Abstract: The outbreak and spread of foodborne diseases is a serious concern for global healthcare and security. Finding novel antimicrobial agents with diverse mechanisms of action against the current spoilage and foodborne bacterial pathogens is a central strategy to overcome the problems of antibiotic resistance. Soil actinomycetes are the major antimicrobial producers with great biopreservative and medical value. This study was aimed at isolating Streptomyces from soil samples of northwestern Ethiopia against spoila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In vitro research has reported inhibition zones ranging from 3.3 ± 1.0 to 13.0 ± 1.4 mm when various Bacillus strains were used against S. Typhimurium [40]. Although similar studies with S. griseus against Salmonella were not found, scientific records suggest the antimicrobial efficacy of this bacterium [41,42].…”
Section: Discussionmentioning
confidence: 98%
“…In vitro research has reported inhibition zones ranging from 3.3 ± 1.0 to 13.0 ± 1.4 mm when various Bacillus strains were used against S. Typhimurium [40]. Although similar studies with S. griseus against Salmonella were not found, scientific records suggest the antimicrobial efficacy of this bacterium [41,42].…”
Section: Discussionmentioning
confidence: 98%
“…Food-borne diseases (FBD) refer to illnesses caused by consuming pathogenic microorganisms, such as bacteria, fungus, viruses, and parasites, or their toxins in the case of bacteria and fungi (1)(2)(3). Additionally, FBD is caused by unprotected food handling and processing, and poor Sanitary conditions (4).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic and spoilage-causing agents must be controlled in a variety of foods to ensure food quality and safety [1][2][3][4]. The sporadic prevalence of microbial pathogens in food and the increased incidence of antibiotic-resistant strains and their genes have posed serious concerns for public health.…”
Section: Introductionmentioning
confidence: 99%